2020
DOI: 10.1074/jbc.ra120.014747
|View full text |Cite
|
Sign up to set email alerts
|

The plant pathogen enzyme AldC is a long-chain aliphatic aldehyde dehydrogenase

Abstract: Aldehyde dehydrogenases are versatile enzymes that serve a range of biochemical functions.  Although traditionally considered metabolic housekeeping enzymes because of their ability to detoxify reactive aldehydes, like those generated from lipid peroxidation damage, the contributions of these enzymes to other biological processes are widespread.  For example, the plant pathogen Pseudomonas syringae strain PtoDC3000 uses an indole-3-acetaldehyde dehydrogenase to synthesize the phytohormone indole-3-acetic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Likewise, Pseudomonas syringae strain PtoDC3000 employs an indole-3-acetaldehyde dehydrogenase ( AldA ) to produce auxin indole-3-acetic acid to escape the host defense [ 141 ]. The AldC gene, homologous to AldA, was shown to function as a long-chain aliphatic aldehyde dehydrogenase, which likely contributed to the feeding of the pathogen on the aliphatic compounds in the plant apoplast [ 142 , 143 , 144 ]. Comparative and evolutionary studies of ALDH between plant and fungal or bacterial plant pathogens may help identify lineage-specific inhibitors to target the plant pathogen enzyme and control plant disease.…”
Section: Aldh Roles In Biotic Stress Responsesmentioning
confidence: 99%
“…Likewise, Pseudomonas syringae strain PtoDC3000 employs an indole-3-acetaldehyde dehydrogenase ( AldA ) to produce auxin indole-3-acetic acid to escape the host defense [ 141 ]. The AldC gene, homologous to AldA, was shown to function as a long-chain aliphatic aldehyde dehydrogenase, which likely contributed to the feeding of the pathogen on the aliphatic compounds in the plant apoplast [ 142 , 143 , 144 ]. Comparative and evolutionary studies of ALDH between plant and fungal or bacterial plant pathogens may help identify lineage-specific inhibitors to target the plant pathogen enzyme and control plant disease.…”
Section: Aldh Roles In Biotic Stress Responsesmentioning
confidence: 99%
“…Recent work identified the AldC enzyme from P. syringae strain Pto DC3000 as a long-chain aliphatic ALDH [ 28 ]. To compare the activity of AldA with AldC, wild-type AldA was assayed using octanal as a substrate; this is the preferred substrate of AldC [ 28 ]. Although AldA displayed activity with octanal ( Table 2 and Supplementary Figure S2A,B), it was 37-fold less efficient as a substrate compared with indole-3-acetaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…This would account for the change in selectivity for octanal as a substrate versus indole-3-acetaldehyde in the AldA F169W mutant. Interestingly, the corresponding residue at this position in AldC from P. syringae , which prefers octanal versus other aliphatic aldehydes as a substrate, is a tryptophan [ 28 ]. Comparison of the k cat / K m for the AldA F169W mutant (2610 M −1 s −1 ) with that of AldC (924 M −1 s −1 ; [ 28 ]) suggest that the identity of the residue at this position of the substrate binding site of these enzymes is critical for substrate preference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of AldA was established to be a nicotinamide adenine dinucleotide (NAD + )-dependent IAAld dehydrogenase that produces IAA [ 11 ]. In 2020, biochemical and structural characterization of AldC by Lee et al revealed it to be a long-chain aliphatic ALDH [ 32 ]. IAA produced by P. syringae has been reported to promote the virulence in Arabidopsis thaliana by two different mechanisms—one, it up-regulates the virulence gene expression in the bacterium, and second, it suppresses salicylic acid-mediated plant defenses by activating auxin signaling in the host plant (via the TIR1/AFB auxin co-receptor system) [ 8 , 11 ].…”
mentioning
confidence: 99%